Textural and origin of Cheshmeh Khorzan conglomerate (Arak Mighan Playa watershed) by multivariate statistical method - Feridon Ghadimi; Farzaneh Esmaeli (Journal of stratigraphy and sedimentology researches, 2022)
AbstractCheshmeh Khorzan conglomerate is located in the Arak Mighan Playa watershed. Determining the texture characteristics and origin of conglomerates is one of the objectives of this study. In the Pliocene loose conglomerate, the particle diameters of the conglomerates varied in a wide range of granule, pebble, cobble and boulders in 51 areas. In addition, the components of conglomerates are mostly good rounded and poorly sorted. Regression analysis and probability level tests such as Student and Fisher test at 95% confidence level showed no significant relationship between roundness and particle diameter with transporting distance. The conglomerate is re-transported in the river and alluvial fan environment. They are close to their source, and their secondary components result from erosion of compact and old conglomerates. Multivariate statistical analyzes showed that the conglomerate components were rich in sandstone (45%), andesite (37%), limestone (7%), tuff (5%), rhyolite (3%), chert and basalt (3%). They have been obtained from the erosion of older formations in Central Iran. Good roundness shows high groundwater potential and high abundance of volcanic fragments indicate the good potential of the placer in the area.Keywords: Texture of conglomerate, Factor analysis, conglomerate source, Cheshmeh Khorzan, Arak Mighan Playa watershed.  IntroductionThe composition and texture of conglomerates indicate the source rock, their origin and the processes that shape them, and their potential as aquifers, as well as the presence of placers such as gold, uranium and iron in the form of minerals such as ilmenite and magnetite. Geochronological, petrographic, geochemical and isotopic studies are very effective in determining the source rock and diagnosing different types of conglomerate composition (Gangwang et al. 2010). Components of conglomerates play a significant role in determining tectonic processes and their type of activity (Zhang et al. 2020). Analysis of the location and geographical transport conditions of the region can be determined with the help of conglomerate components (Minghuai et al. 2010). The composition, structural features and fabric of conglomerates can determine the type of conglomerate and their origin (Bayet-Goll et al. 2015). Evaluation of components of a loose Pliocene conglomerate of Cheshmeh Khorzan in terms of particle diameter, roundness and their relationship with distance is one of the obvious aims of this research. Determination of constituent particles’ origin by multivariate statistical methods such as correlation coefficient, regression, factor and cluster analysis are other aims. This research provides a suitable subject for studying and evaluating the water potential of other areas around the Ashtian city and especially for investigating the origin of magnetite and ilmenite placers in the Cheshmeh Khorzan area. Material & MethodsIn this study, 51 samples were analyzed. Due to vegetation and debris cover on the conglomerates, sampling was performed in areas where the conglomerate was exposed. In the field operations, particle diameter variables (maximum, minimum and average diameter), roundness and composition of gravels in loose conglomerate were determined. In one square meter to four square meters of each area, it determined the number of gravels and different compounds. Their roundness of gravels was determined using tables and different equations. Univariate, bivariate and multivariate statistical parameters such as factor analysis and cluster analysis were determined by Statistical software version 12. In bivariate statistics, a regression equation was established between gravel diameters, roundness and distance, and the equations were evaluated by Fisher, Student t-test and probability level test (p-value). The Student's t-test of each variable was compared with the critical value at a 95% confidence level (5% error). In multivariate statistics, step-by-step factor analysis was performed by reducing the dimensions of data and cluster analysis based on intra-group similarity and inter-group differences. Discussion of Results & ConclusionThis study showed the minimum diameter of the gravel particles is 4 mm and the maximum is 1500 mm, and the average particle diameter is 5 mm is 51 areas of the conglomerate outcrops. Rock grains account for about 44% boulder, 27% cobble, 15% pebbles and 14% granule volume. Characteristics of Cheshmeh Khorzan conglomerate are textural evidence such as good roundness, poor sorting and a wide range of different particles. In the regression equation, it was found that there is no significant relationship between grain diameter and roundness at the 95% confidence level. The high roundness of the gravels indicates the second cycle of grain transport in the conglomerate. Factor analysis and cluster analysis were used to differentiate the origin of conglomerate composition. In the first stage of stepwise factor analysis, three factors were identified. In the first factor, it determined limestone gravel with a positive factor has a 0.88 factor load and sandstone gravel with a negative sign has 0.83 factor load. The share of this factor is 26.84% of the population. The role of other components is low in the first factor due to the less than 0.7 factor load. Also, due to the opposite sign of sandstone and limestone factor load, it is evident that the first factor has two origins. In the second factor, the combination of tuff with 0.81 factor load and rhyolite with 0.79 factor load had the largest share and its share is 23.14%. Andesitic composition in the third factor with a negative load of 0.88 with a 17.33% share has the most population. Three factors account for about 67.31 percent of the conglomerate population. In the first stage of factor analysis, the combination of basalt and chert had the lowest factor load, so it was removed from the conglomerate community. In the second stage of factor analysis, three factors were obtained by removing the basalt and chert composition. The diversity of the composition of gravels indicates multiple origins and from erosion of the formations in the Central Iran zone. Therefore, the loose conglomerate of Cheshmeh Khorzan in the Upper Pliocene is a secondary cycle and its components were the result of primary conglomerate erosion such as the consolidated Lower Pliocene conglomerates from the east or conglomerates from older formations such as the Upper Red Formation in the north (Ashtian basin). The Miocene–Pliocene orogenic phase of the Cheshmeh Khorzan region is tensile and have caused the replacement of volcanic material. Erosion and transport of older volcanic material and rocks during the tectonic phase has led to the formation of conglomerates in the area. In order to determine the environmental conditions and characteristics of the Cheshmeh Khorzan conglomerate, it is suggested to prepare different types of rock facies in different sequences and sedimentary models. The good roundness of conglomerates can be one of the reasons for the high potential of groundwater for wells drilled in the conglomerates of the region and water exploration in other areas of Ashtian city. The high abundance of volcanic fragments, especially andesitic fragments in conglomerates containing placer magnetite and ilmenite can be a good guide for the region of origin and route of transport and re-cycle to the Cheshmeh Khorzan region.   .